Amendments to the Serbian Law on Prohibition of Discrimination: A step forward? - Rašević Živorad; Vlajnić Jelena (Trendovi u Poslovanju, 2022)
The amendment to the Law on Prohibition of Discrimination ("Official Gazette of RS" No. 52/21) amended and supplemented almost half of the provisions of the general anti-discrimination law of Serbia, in order to harmonize with European Union and domestic laws. This paper examines the legal justification and expediency of this intervention of the legislator and assesses the extent to which the accepted novelties have improved protection against discrimination. The results of the research indicate positive prospects, mainly due to the specifying of provisions, the expansion of the scope of antidiscrimination law and the authority of the Commissioner for the protection of equality, the clarification of the concepts of discrimination and affirmative action, the tightening of penal policy, and the recognition of statistical records as evidence. However, the realisation of these positive effects seems dubious, because the opportunity to concretize concepts of the binding anti-discrimination law of the Council of Europe and the Constitution of Serbia was missed.